Anthropophagic-Perspectivistic Poetics for a Re-Vision of the Brazilian Theater: the scene of origin - Gardel, André (Revista Brasileira de Estudos da Presença, 2022)
ABSTRACT – Anthropophagic-Perspectivistic Poetics for a Re-Vision of the Brazilian Theater: the scene of origin – This text presents a plan of construction of a Poetics, whose purpose is to effect a Re-Vision, in five key moments, of the Brazilian Theater. To do this, we seek to establish a scene of origin, outlined after the meeting – impregnated with attraction and repulsion – that takes place in Brazil, from the sixteenth century, between Amerindian and European civilizations. Two metaphysics and forms of expression thus form the intensive and pantheatrical basis of a Poetics that projects a notion of Brazilian theater in a constant state of struggles of perspectives, symbolized, in its origins, by two anthropophagic mouths interdevouring: the mercantilist Christian Eucharist and the Amerindian cosmopolitical.